Warsaw Jews Expelled from Switzerland to the General Government - Jan Grabowski; Barbara Engelking (Zagłada Żydów)
After the defeat in the Polish-German war of 1939, many people made plans to escape from the territories occupied by the Germans. As a rule, people escaped to the East, and among “castaways”, travelling the “Eastern route”, the percentage of Jews was exceptionally high, for quite obvious reasons. Some managed to leave the Soviet Union for Sweden, Palestine or even Japan. This, however, is another story.